2019
DOI: 10.1002/chem.201902230
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Thioredoxin Reductase‐Like Activity with Cyclic Selenenyl Sulfides: Participation of an NH⋅⋅⋅Se Hydrogen Bond through Stabilization of the Mixed Se−S Intermediate

Abstract: At the redox-active centero ft hioredoxin reductase (TrxR), as elenenyl sulfide( SeÀS) bond is formed between Cys497 and Sec498, which is activated into the thiolselenolate state ([SH,Se À ]) by reactingw ith an earby dithiol motif ([SH Cys59 ,SH Cys64 ]) presenti nt he other subunit. This process is achievedt hrough two reversible steps:a na ttack of a cysteinyl thiol of Cys59 at the Se atom of the SeÀSb ond and as ubsequenta ttack of ar emaining thiol at the Sa tom of the generated mixed SeÀSi ntermediate. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
(45 reference statements)
1
28
0
1
Order By: Relevance
“…Interestingly, the E °′ of compound 1 was significantly increased via the conjugation of amino acids, suggesting that compounds 2 a – d function as good oxidants for SS‐formation in proteins. 77 Se NMR spectra of the compounds showed that the chemical shifts of 1 (δ Se =281 ppm) and 2 a – d were almost comparable (see supporting information), implying that the increase in E °′ values would be due to the thermodynamic stabilization of the reduced state by a weak interaction, such as NH•••Se hydrogen bond, which is found in the reduced form of cyclic Se−S compounds . Unexpectedly, Ala‐conjugation further raised the E °′ compared to that with Lys‐ and Arg‐conjugations.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Interestingly, the E °′ of compound 1 was significantly increased via the conjugation of amino acids, suggesting that compounds 2 a – d function as good oxidants for SS‐formation in proteins. 77 Se NMR spectra of the compounds showed that the chemical shifts of 1 (δ Se =281 ppm) and 2 a – d were almost comparable (see supporting information), implying that the increase in E °′ values would be due to the thermodynamic stabilization of the reduced state by a weak interaction, such as NH•••Se hydrogen bond, which is found in the reduced form of cyclic Se−S compounds . Unexpectedly, Ala‐conjugation further raised the E °′ compared to that with Lys‐ and Arg‐conjugations.…”
Section: Resultsmentioning
confidence: 89%
“…77 Se NMR spectra of the compounds showed that the chemical shifts of 1 (δ Se = 281 ppm [7b] ) and 2 a-d were almost comparable (see supporting information), implying that the increase in E°' values would be due to the thermodynamic stabilization of the reduced state by a weak interaction, such as NH *** Se hydrogen bond, which is found in the reduced form of cyclic SeÀ S compounds. [9] Unexpectedly, Ala-conjugation further raised the E°' compared to that with Lys-and Arg-conjugations. This is because that α-amino group also participates in the formation of NH *** Se hydrogen bonds.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Seine Gruppe beschäftigt sich auch mit den molekularen Mechanismen und komplexen Stoffwechselpfaden der Schilddrüsenhormone. Er veröffentlichte kürzlich eine Zuschrift in der Angewandten Chemie über den Nachweis einer Seleninsäure in lebenden Zellen und ein Full Paper in Chemistry — A European Journal über ein Modell der Thioredoxin‐Reduktase‐artigen Aktivität mit cyclischen Selensulfiden . Mugesh war Mitglied des Internationalen Beirats von ChemPlusChem (2012–2015), und er wird ab 2020 dem Redaktionsbeirat von Chemistry—A European Journal angehören.…”
Section: Ausgezeichnet …unclassified